Maqasid al-shari’ah theoretical framework for teaching and the parameters for measuring Key Intangible Performance (KIP) in teaching - Ali, Mohammed Farid; Zakariya, Luqman; Ahmad H. Osman, Rrahmah (Siauliai University, 2022)
Application of Maqasid al-Shari'ah to determine and measure the Key Intangible Performance (KIP) in general and in teaching precisely is considered a topical issue in the current era. KIP acknowledges the prospective intangible means that contribute to holistic productivity of institutions and individuals. This paper reviews the available literature to develop a Maqasid al-Shari'ah theoretical framework for teaching. This paper employs qualitative methodology, which basically relies on textual analysis. Then combines this with Sekaran’s behavioural science operationalization method as a research design to develop a Maqasid based parameter for the Key Intangible Performance (KIP) in teaching. The findings show that teaching and learning (T&L) is based on three dimensions, Faith and tawhid of the teacher (D1), goal of T&L to produce balanced human (insan sejahtera) (D2) and content of T&L to be in line with the Islamic worldview (D3). The indicators of these dimensions are three, Curriculum/programs, human resource and material resource.